Mulher, negra e puta: duas histórias sobre-vivência. - Souza, Rafaela dos Santos Silva (2021)
Female prostitution is a reality present in the history of Brazil since the colonial period, and its existence is widely known and, many times, tolerated. The woman who prostitutes herself, however, suffers from the stigma of a whore and, stigmatized, carries out her activity in marginality. This work emerged with the objective of understanding how the research participants were constituted throughout their lives as women, black and sex workers. In this sense, the social markers about what is the signifier woman, black and whore come into discussion with their counterparts: racism, gender inequality and social inequality strongly present in Brazilian society. Prostitution is not the only focus of discussion in this work, but the means by which we are invited to know the life story of two black women, with low purchasing power, over sixty years of age and with more than 40 years of experience. years of prostitution. Their stories have been presented since the period before going into prostitution. Then the experience of prostitution and the day-to-day experiences in parallel with their personal lives. In a third moment, we are faced with a retrospective look, which seeks meaning for a story in part already passed, presenting the current moment of the research participants' lives. From their stories, constellations of meaning were revealed and named as “The big window: prostitution”, “Battle”, and “In-visibility and senses”. Supported by the theoretical perspective of Hannah Arendt, Judith Butler and Simone de Beauvoir, we understand that physical and verbal violence is constituted during the life of the research participants as a thread that permeates several moments of these women's lives, revealing a process of violence that is still ongoing. greater directly linked to the historical social, racial and gender inequality present in Brazil that seems to deny the prostitutes of yesterday, and of today, a place of subjects with fundamental rights. It is understood that the invisibility, marginalization and difficulty in bringing issues such as female prostitution to public light ends up denying the women in question the ascension to the condition of humanity. Thus, the present work reveals and denounces the precariousness of this group that shows itself as a violation of human rights.